Dark matter and the deformed Poincaré group - Fernández, Julián Martín (1996)
It has been recently suggested that models of deformed special relativity, based on a deformed Poincare group, could account for the missing mass problem, due to the nonadditivity of energy for large systems predicted by these models. We show that this is not correct and that, in fact, these models predict just the opposite effect.